Faster rehabilitation weight gain during childhood is associated with risk of non-communicable disease in adult survivors of severe acute malnutrition. - Debbie S Thompson; Kimberley McKenzie; Charles Opondo; Michael S Boyne; Natasha Lelijveld; Jonathan C Wells; Tim J Cole; Kenneth Anujuo; Mubarek Abera; Melkamu Berhane; Albert Koulman; Stephen A Wootton; et al. (PLOS Global Public Health)
Nutritional rehabilitation during severe acute malnutrition (SAM) aims to quickly restore body size and minimize poor short-term outcomes. We hypothesized that faster weight gain during treatment is associated with greater cardiometabolic risk in adult life. Anthropometry, body composition (DEXA), blood pressure, blood glucose, insulin and lipids were measured in a cohort of adults who were hospitalized as children for SAM between 1963 and 1993. Weight and height measured during hospitalization and at one year post-recovery were abstracted from hospital records. Childhood weight gain during nutritional rehabilitation and weight and height gain one year post-recovery were analysed as continuous variables, quintiles and latent classes in age, sex and minimum weight-for-age z-scores-adjusted regression models against adult measurements. Data for 278 adult SAM survivors who had childhood admission records were analysed. Of these adults, 85 also had data collected 1 year post-hospitalisation. Sixty percent of participants were male, mean (SD) age was 28.2 (7.7) years, mean (SD) BMI was 23.6 (5.2) kg/m2. Mean admission age for SAM was 10.9 months (range 0.3-36.3 months), 77% were wasted (weight-for-height z-scores<-2). Mean rehabilitation weight gain (SD) was 10.1 (3.8) g/kg/day and 61.6 (25.3) g/day. Rehabilitation weight gain > 12.9 g/kg/day was associated with higher adult BMI (difference = 0.5 kg/m2, 95% CI: 0.1-0.9, p = 0.02), waist circumference (difference = 1.4 cm, 95% CI: 0.4-2.4, p = 0.005), fat mass (difference = 1.1 kg, 95% CI: 0.2-2, p = 0.02), fat mass index (difference = 0.32kg/m2, 95% CI: -0.0001-0.6, p = 0.05), and android fat mass (difference = 0.09 kg, 95% CI: 0.01-0.2, p = 0.03). Post-recovery weight gain (g/kg/month) was associated with lean mass (difference = 1.3 kg, 95% CI: 0.3-2.4, p = 0.015) and inversely associated with android-gynoid fat ratio (difference = -0.03, 95% CI: -0.07to-0.001 p = 0.045). Rehabilitation weight gain exceeding 13g/kg/day was associated with adult adiposity in young, normal-weight adult SAM survivors. This challenges existing guidelines for treating malnutrition and warrants further studies aiming at optimising these targets.